Covid -19 vaccines, public health goods and Catholic social teaching: Why justice must prevail over charity in the global vaccine distribution - Ballano, Vivencio O. (HTS teologiese studies, 2022)
Applying the Roman Catholic Church’s set of moral principles on social concerns called Catholic social teaching (CST) on charity, distributive justice, private property and the common good, and utilising some secondary data and scientific literature, this article argues that establishing distributive justice for the global distribution of the COVID-19 vaccines must be a priority than donating millions of doses in the name of charity to address vaccine scarcity. Catholic social teaching teaches that the right to private property is a basic right but has moral limits and is subordinated to the moral principles on the universal destination of earth’s goods and the common good.Contribution: The current COVID-19 vaccines are developed by people and organisations outside the pharmaceutical companies and largely funded using taxpayers’ money. Thus, by virtue of justice, these vaccines must belong to all nations as global public health goods. Patents are to be suspended to allow poor countries to reproduce the popular vaccines and address the current vaccine shortage.